Ivy + Bean and the ghost that had to go - Barrows, Annie; Blackall, Sophie (San Francisco, CA. : Chronicle Books, 2006)
Second-graders Ivy and Bean set out to expel the ghost who is living in the girls' bathroom at their school.
580
Keywords: Schools -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Ghost stories